2022
DOI: 10.3390/ani12172280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gardenia Pomace Supplementation on Growth Performance, Blood Metabolites, Immune and Antioxidant Indices, and Meat Quality in Xiangcun Pigs

Abstract: To investigate the effect of gardenia pomace (GP) as an unconventional feed of antioxidants, 180 Xiangcun pigs were randomly divided into 3 groups during the finishing period, with 6 replicates per group and 10 pigs per replicate. During the 47-day feeding period, the pigs were fed either a control diet based on corn and soybean meal (control group), or the control diet added with 50 g/kg or 100 g/kg GP (groups GP5 and GP10, respectively). Feed and water were provided ad libitum. One pig per replicate was slau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…In this sense, previous studies have shown that the use of non-conventional feed sources rich in PCs can positively modify some hematological and biochemical parameters in monogastric under stressful situations [22,61]. Therefore, blood metabolites have been considered as indicators of nutritional metabolism and health of animals [62]. In the present study, the values obtained to hormonal levels, hematological and biochemical parameters were within the reference ranges reported for the species and its stage [63].…”
Section: Hematological and Biochemical Variables And Hormone Levelssupporting
confidence: 81%
“…In this sense, previous studies have shown that the use of non-conventional feed sources rich in PCs can positively modify some hematological and biochemical parameters in monogastric under stressful situations [22,61]. Therefore, blood metabolites have been considered as indicators of nutritional metabolism and health of animals [62]. In the present study, the values obtained to hormonal levels, hematological and biochemical parameters were within the reference ranges reported for the species and its stage [63].…”
Section: Hematological and Biochemical Variables And Hormone Levelssupporting
confidence: 81%
“…The antioxidant application of unconventional fermented feed in animal production is a key measure. This type of feed protects animal cells from oxidative damage by providing a rich source of antioxidants [ 61 ] such as vitamin C, vitamin E, and polyphenolic compounds that effectively inhibit the production of free radicals. In addition, the preparation of unconventional fermented feed may degrade the anti-nutritional factors and toxins in feed, reduce the load of oxidative stress in animals [ 62 ], and further reduce the incidence of oxidative damage.…”
Section: The Effects and Mechanism Of Fermentation On The Improvement...mentioning
confidence: 99%
“…Likewise, under these conditions, the platelet content is modified. In this sense, previous studies have shown that the use of non-conventional feed sources rich in PCs can positively modify some hematological and biochemical parameters in monogastric under stressful situations [31,66]. Therefore, blood metabolites have been considered as indicators of nutritional metabolism and health of animals [67].…”
Section: Hematological and Biochemical Variables And Hormone Levelsmentioning
confidence: 99%